2009
DOI: 10.1016/j.bmcl.2009.02.056
|View full text |Cite
|
Sign up to set email alerts
|

8-[2-(4-Aryl-1-piperazinyl)ethyl]-2H-1,4-benzoxazin-3(4H)-ones: Dual-acting 5-HT1 receptor antagonists and serotonin reuptake inhibitors—Part II

Abstract: 8-[2-(4-Aryl-1-piperazinyl)ethyl]-2H-1,4-benzoxazin-3(4H)-ones have been identified as highly potent 5-HT(1A/B/D) receptor antagonists with and without additional SerT activity and a high degree of selectivity over hERG potassium channels. Modulation of the different target activities gave compounds with a range of profiles suitable for further in vivo characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…During the last twenty years several chemical scaffolds are known to bind 5-HT 1A R sites, among these, arylpiperazine derivatives represent one of the most studied skeletons [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the last twenty years several chemical scaffolds are known to bind 5-HT 1A R sites, among these, arylpiperazine derivatives represent one of the most studied skeletons [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…SB-269970 and SB-656104-A are 5-HT 7 receptor antagonists that exhibit antidepressant-like activity . Moreover, recent studies suggest that selective blockade of 5-HT 7 R may have a synergistic effect with the inhibition of 5-HT reuptake in animal model of depression .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown the antidepressant efficacy of dual 5-HT1/SSRIs compounds. 17 One of the most important advantages of these compounds is that they may behave as novel antidepressantlike agents with a faster onset of action. 18 …”
Section: Introductionmentioning
confidence: 99%
“…This special reactivity allows this class of compounds to be useful as antimicrobial [1], anti-platelet aggregation [2], human leukocyte elastase inhibitors [3], receptor agonist active [4], receptor antagonist active [5-9], pesticides [10], tissue culture protective and in vivo model of neurodegeneration [11] and improve the umbilical vein endothelial cells [12]. In this paper, we report both the uses of 2-ethoxy-(4 H )-3,1-benzoxazin-4-one (1, Scheme 1) in the synthesis of some quinazolinone derivatives and the screening of antimicrobial activity of some of the newly synthesized derivatives against Gram-negative and Gram-positive bacteria as well as fungi by means of the disc diffusion method.…”
Section: Introductionmentioning
confidence: 99%